Bidirectional Interactions Between Thymocytes and Thymic Epithelial Cell Lines in Vitro - Čolić, Miodrag (Hindawi Publishing Corporation, 1998)
In vitro interactions of thymocytes and thymocyte hybridomas with cortical (R-TNC.1) and medullary (TE-R 2.5) rat thymic epithelial-cell (TEC) lines were studied. It was found that the cortical line had better adhesion capability. It bound exclusively immature CD4(+)CD8(+) αβTCR(10) thymocytes, induced apoptosis of a subset of these cells, and stimulhted proliferation of the BWRT (CD4(-)CD8(-) αβTCR(-)) hybridoma. The medullary line bound both immature and mature thymocytes, decreased their apoptosis, and induced apoptosis of the BWRT 8 (CD4(+)CD8(10) αβTCR(hi)) hybridoma. Thymocyte differently modulated cytokine production by TEC lines, upregulating the secretion of IL-1 by R-TNC.1 and IL-6 by TE-R 2.5 cells. Finally, coculture of thymocytes with TEC lines resulted in different patterns of protein-tyrosine phosphorylation in thymocytes. These results show the existence of mutual bidirectional interactions between thymocytes and TEC lines in vitro, but these processes differed depending on phenotypic characteristics and origin of TEC lines used.